2006
DOI: 10.1007/s10439-006-9202-9
|View full text |Cite
|
Sign up to set email alerts
|

Optical Vibrocardiography: A Novel Tool for the Optical Monitoring of Cardiac Activity

Abstract: We present an optical non-contact method for heart beat monitoring, based on the measurement of chest wall movements induced by the pumping action of the heart, which is eligible as a surrogate of electrocardiogram (ECG) in assessing both cardiac rate and heart rate variability (HRV). The method is based on the optical recording of the movements of the chest wall by means of laser Doppler interferometry. To this aim, the ECG signal and the velocity of vibration of the chest wall, named optical vibrocardiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
65
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 40 publications
1
65
0
1
Order By: Relevance
“…Laser vibrometry was first applied in different engineering fields, such as modal analysis, vibration and noise testing, characterizing loudspeakers, and assessing piezoceramic transducers [25]. Recently, laser vibrometry has gained traction in biomedical and bioengineering applications, such as auditory research [26,27], dentistry [28,29], cardiology [30][31][32], as well as elastography and rheology [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Laser vibrometry was first applied in different engineering fields, such as modal analysis, vibration and noise testing, characterizing loudspeakers, and assessing piezoceramic transducers [25]. Recently, laser vibrometry has gained traction in biomedical and bioengineering applications, such as auditory research [26,27], dentistry [28,29], cardiology [30][31][32], as well as elastography and rheology [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…First studies using optical vibrometry (laser Doppler vibrometry) has been reported for the identification of the arterial pressure waves (Tomasini et al in 1998). While a novel method, called vibrocardiography (VCG), has been later proposed to measure the velocity of displacement of the skin in correspondence of the chest wall (Scalise et al, 2005a;2005b;Morbiducci et al, 2006;Scalise and Morbiducci, 2008). VCG has been demonstrated to be valid for the assessment of the cardiac frequency and variability and in Cardiac Resinchronization Theraphy as support in pacemaker programming after installation (Bocconcelli et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While most studies that suggest heartbeat-based security (HBBS) for mHealth assume that physical contact is required to generate the same identifier from IPIs, an increasing number of studies suggest that heartbeats may be measured remotely using, for example, Doppler radar [8], capacitive coupling [9], optical vibrocardiography [10], ballistocardiography [11], (thermal) imaging [12], [13] and even through detecting minute difference in a person's voice [14]. Such techniques are primarily intended to have a positive impact on healthcare, for example, by monitoring an infant incubator without touching the frail infant [15].…”
Section: Introductionmentioning
confidence: 99%